When to regulate airports: A simple rule - Uwe Kratzsch; Gernot Sieg (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2009)
Landing fees at airports are regulated almost all over the world since airports are assumed to abuse their market power. We find that monopolistic airports have an incentive to restrain landing fees when they generate additional non-aviation revenues and that the optimal landing fee decreases in the degree of complementarity of aviation and non-aviation. Furthermore, we show that monopolistic airports will not have an incentive to abuse their market power anymore so that a price regulation becomes inappropriate as soon as non-aviation revenues increase above 50% of all airport revenues.
urn:nbn:de:gbv:084-25406
Keywords: L93; D42; L51; 330; airport regulation; aviation and non-aviation revenues; complementarity of aviation and non-aviation; locational rents